ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATIONAL INSTITUTIONS: OPPORTUNITIES AND PROBLEMS (TAMADDUN NURI JURNALI, 2025)
This article examines the opportunities and challenges of Artificial Intelligence in higher education and analyzes the impact of new technologies on teaching and learning. It also highlights examples of Artificial Intelligence implementation to ensure equitable and high-quality education, emphasizing its importance and potential for improving educational outcomes.